Using Conceptual Blending Theory to help college students design online communication models - Li, Chenxi; bin Azraai, Nur Zaidi (Dirasat: Human and Social Sciences, 2024)
Objective: This study examines modal social media visuals using Conceptual Blending Theory (CBT) and its theoretical foundation, Conceptual Blending Network, to improve college students’ visual communication on social media. Methods: The study explores social media visuals and CBN’s mechanism. It goes beyond meme design to explain the key factors and reinforcement strategies needed to use CBN to create social media visuals. This study creates an empirical experimental model for validation, a novel approach. The experimental model teaches college students how to create engaging social media visuals. Three university teachers in relevant fields collaborated on the research project with 232 diverse undergraduates who completed surveys and interviews. Results: The study found that undergraduates recognise the importance of visual language organisation for accurately conveying complex information on social media. Collaboration with experts and the introduction of CBT and CBN helped university students accept this advanced visual language organisation method for social media visuals. Conclusion: Participants’ understanding, comprehension, and practical exposure to the proposed methodology significantly reduced their difficulties in designing compelling social media visuals. This research helps us understand social media visual dynamics and informs educators and practitioners who want to improve digital visual communication.